I Gincóleo: gincana de coleta de óleo usado no câmpus de Araraquara - Santos, Denise Gabriela [UNESP]; Cruz, Gustavo Henrique Calegarette da [UNESP]; Marchetto, Patricia Borba [UNESP]; Terence, Ana Cláudia Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In 2005, the "GINCÓLEO" was the first edition of a competition part of the list of activities developed by the project" Cooperative administrations in Acacia ". The activity was developed by volunteers who were 1st year Public Administration students of FCL / CAr. The objectives of the activity consisted of collecting used oil in the university community and assist in spreading acacia cooperative, which is responsible for selective collection in the city of Araraquara. All the materials collected were donated to the cooperative, in an effort to supporting and strengthening its huge task. In addition, it contributed with the expansion of environmental awareness activities, the process of social and economic inclusion of collectors and reducing environmental impacts.

A GINCÓLEO foi a primeira edição da gincana que integra o rol de atividades desenvolvidas pelo Projeto “AdministrAÇÕES na Cooperativa Acácia”, no ano de 2015. A atividade foi desenvolvida por alunos do 1º ano do curso de Administração Pública da FCL/CAr, voluntários do projeto. Os objetivos da atividade consistiram em arrecadar óleo usado na comunidade universitária e auxiliar na divulgação da Cooperativa Acácia, responsável pela coleta seletiva na cidade de Araraquara. Todo o material recolhido foi doado à cooperativa, apoiando e fortalecendo o trabalho por ela desenvolvido. Além disso, contribuiu-se com a ampliação das atividades de educação ambiental, o processo de inserção social e econômica dos catadores, e a redução dos impactos ambientais.
Keywords: Cooperative Acacia; Used oil; Gincóleo; Cooperativa Acácia; Óleo usado; Gincóleo